Legal Protection for Credit Card Issuing Banks in Customer Default - Jamal Abidin (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study is to discusses the legal protection for credit card issuing banks in cases of customer default. In practice, customer defaults frequently occur, causing financial losses for issuing banks. This research aims to identify the legal measures that banks can take to protect their interests. The research methodology used is normative juridical with a descriptive analytical approach. The results indicate that banks have several legal recourses, such as resolving disputes through litigation and non-litigation avenues, and implementing protective clauses in credit card agreements. Additionally, existing legislation provides a strong legal foundation for banks to assert their rights. The article recommends that banks be more proactive in drafting clear and detailed agreements, as well as strengthening monitoring and collection mechanisms to minimize the risk of default.